The importance of basic values for the subjects of the educational environment as a condition of its security - Elvira N. Gilemkhanova; Reseda M. Khusainova; Elvira H. Bashlay (Saratov State University, 2021)
The increasing complexity of quantitative and qualitative characteristics of the educational environment prompts the research aimed at investigating the modern social and cultural landscape and identifying acmeological mechanisms of social and psychological aspects of the school safe climate. The theoretical framework of the study was based on the concept of "cultural traditions" proposed by D. B. Zilberman and devoted to normative and value types of attitudes to reality. The purpose of the study is to establish the correlation between the assessment of the social and psychological aspects of the school safe climate and the value and normative types of attitudes to reality. The latter are seen as the ways for the subjects of the educational process to express the attitude to the basic values. Research hypotheses: 1) Subjects of the educational environment who regard basic values as significant represent a value type; 2) The value type of the personality determines the educational environment as a safer one. The study sample includes: 1177 students aged 13 to 16 (60% of boys, 40% of girls, average age 14.9), 925 parents aged 28 to 57 (93% of females, 7% of males; average age 39.0), 136 teachers aged 23 to 74 (95% of females, 5% of males; average age 38.7) from Kazan. Research methodology: the test "Value Orientations" (by M. Rokich), the original questionnaire on the social and psychological aspects of the school safe climate (by E. N. Gilemkhanova). Evidently, the subjects of the educational environment who regard basic values as significant represent a value type as opposed to a normative type. The research shows that the value type of attitude determines the identification of the educational environment as a safer one. The scientific novelty of the study lies in the fact that the results obtained open up the possibility for interpreting D. B. Zilberman's concept in the context of acmeological determinants of social and psychological aspects of the school safe climate. The results of the study can be used to provide psychological and pedagogical support to the subjects of the educational process. Additionally, they are of importance for those implementing complex measures to organize a safe educational environment of the school.